Icosahedral 60-meric porous structure of designed supramolecular protein nanoparticle TIP60. Issue 79 (15th September 2021) - Obata, Junya; Kawakami, Norifumi; Tsutsumi, Akihisa; Nasu, Erika; Miyamoto, Kenji; Kikkawa, Masahide; Arai, Ryoichi
Abstract : The icosahedral 60-meric porous structure of the designed supramolecular protein nanoparticle TIP60 was solved using cryo-EM. Abstract : Supramolecular protein nanoparticles and nanocages have potential in a broad range of applications. Recently, we developed a uniform supramolecular protein nanoparticle, TIP60, symmmetrically self-assembled from fusion proteins of a pentameric Sm-like protein and a dimeric MyoX-coil domain. Herein, we report the icosahedral 60-meric structure of TIP60 solved using single-particle cryo-electron microscopy. Interestingly, the structure revealed 20 regular-triangle-like pores on the surface. TIP60 and its mutants have many modifiable sites on their exterior and interior surfaces. The TIP60 architecture will be useful in the development of biomedical and biochemical nanoparticles/nanocages for future applications.